A Narrative Review of Preventive Central Lymph Node Dissection in Patients With Papillary Thyroid Cancer - A Necessity or an Excess - Dolidze, David D.; Shabunin, Alexey V.; Mumladze, Robert B.; Vardanyan, Arshak V.; Covantsev, Serghei D.; Shulutko, Alexander M.; Semikov, Vasiliy I.; Isaev, Khalid M.; Kazaryan, Airazat M. (Frontiers in Oncology, 2022)
Objective: This review article summarises the latest evidence for preventive central lymph node dissection in patients with papillary thyroid cancer taking into account the possible complications and risk of recurrence. Background: Papillary thyroid cancer is the most frequent histological variant of malignant neoplasms of the thyroid gland. It accounts for about 80-85% of all cases of thyroid cancer. Despite good postoperative results and an excellent survival rate in comparison with many other malignant diseases, tumor metastases to the cervical lymph nodes are frequent. Most researchers agree that the presence of obvious metastases in the lymph nodes requires careful lymph node dissection. It was suggested to perform preventive routine lymphadenectomy in all patients with malignant thyroid diseases referred to surgery. Methods: It was performed the literature review using the “papillary thyroid cancer”, “central lymph node dissection”, “hypocalcemia”, “recurrent laryngeal nerve paresis”, “metastasis”, “cancer recurrence” along with the MESH terms. The reference list of the articles was carefully reviewed as a potential source of information. The search was based on Medline, Scopus, Google Scholar, eLibrary engines. Selected publications were analyzed and their synthesis was used to write the review and analyse the role of preventive central lymph node dissection in patients with papillary thyroid cancer. Conclusions: The necessity of preventive central lymph node dissection in patients with differentiated papillary thyroid carcinoma is still controversial. There is much evidence that it increases the frequency of transient hypocalcemia. Since this complication is temporary, its significance in clinical practice is debatable. It can also be assumed that an extant of surgery in the neck area is associated with an increased risk of recurrent laryngeal nerve injury. However, most studies indicate that this injury is associated more with thyroidectomy itself than with lymph node dissection. Recurrent laryngeal nerve dysfunction is also a temporary complication in the vast majority of cases. At the same time, a large amount of data shows that central lymph node dissection reduces the risk of thyroid cancer recurrence in two times.